New Cotton Varieties - A Guarantee of a Rich Harvest - Abdurashid, Kasimov; Ilkhomjon, Abdurakhmanov; Bakhtiyorjon, Kasimov (American Journal of Biodiversity, 2025)
In the article: The newly created lines were studied in the “Selection Variety Testing” experiment at the Andijan Scientific and Experimental Station of the PSUEAITI in 2022-2024. The growth and development of the lines and their beneficial characteristics for the economy are presented. Currently, due to changes in weather and climate, the degree of adaptation of newly created varieties and lines to this environment, that is, the development of new lines, including changes in flowering and ripening periods as a result of the influence of weather and changing climate on plant development, is presented (Table 1). The yield elements in plants at the beginning of the autumn season, i.e. the number of mature bolls and the number of those that ripen and open, are also presented. The effect of weather changes on economically valuable traits is also taken into account. In particular, information is provided on the number and quality of growth traits under the influence of changing weather conditions, such as the period of action, wilt infestation, cotton per boll, fiber yield and length.